Aflibercept versus Ranibizumab as a Second Line Therapy After Bevacizumab for Diabetic Macular Edema - Alsaedi NG (Dove Medical Press, 2021)
Nasser G Alsaedi,1,2 Ruba M Alselaimy,3 Abdulaziz A Alshamrani,1 Muhammed AlAjmi,4 Rajiv Khandekar,1 Hassan Al-Dhibi,1 Abdulelah A Al-Abdullah1 1King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 2King Abdullah Medical City, Makkah, Saudi Arabia; 3College of Medicine, King Saud University, Riyadh, Saudi Arabia; 4Albahar Eye Centre, Kuwait City, KuwaitCorrespondence: Abdulelah A Al-AbdullahVitreoretinal and Uveitis consultant, Vitreoretinal division, King Khaled Eye Specialist Hospital, P. O. Box 7191, Riyadh, 11462, Saudi ArabiaTel +966114821234 extension 2655Email hasadoc@gmail.comPurpose: To compare the visual and anatomic outcomes of aflibercept versus ranibizumab as a second line treatment for persistent diabetic macular edema (DME) after initial bevacizumab injections.Methods: In this retrospective cohort study, patients with center-involved DME of ≥  300 μm thickness after bevacizumab intravitreal injections in 2015– 2019 were included. Those treated with ranibizumab (R) and aflibercept (A) were grouped as group R and group A, respectively. The change in central macular thickness (CMT) measured by optical coherence tomography (OCT) and the best corrected distance visual acuity (BCVA) before and after three-monthly anti-VEGF injections (anti-VEGF) in group R and group A were compared and reviewed.Results: There were 80 eyes of 75 patients in group R and 80 eyes of 72 patients in group A. The initial bevacizumab injections in group R and group A varied significantly (p = 0.01). The median change of the CMT after the three injections was not significantly different in group R (80 μm) and group A (81.5μm) (p = 0.7). The improvement of BCVA in group R and group A was not significant (p = 0.5). Dry macula was noted in 1 vs 14 eyes in group R vs group A.Conclusion: After treating refractory DME with initial bevacizumab injections, 3 injections of either aflibercept or ranibizumab had similar anatomic and functional outcomes. Aflibercept achieved dry macula in more eyes with refractory DME compared to ranibizumab.Keywords: aflibercept, bevacizumab, persistent DME, ranibizumab, VEGF switch, vascular endothelial growth factor